Auswirkungen von Privatisierungen auf die kommunale Wirtschaftspolitik. - Börgmann-Dehina, Elias (Kovac, 2015)
Frage ist, welchen Umfang das wirtschaftspolitische Instrumentarium der Kommunen hat, und ob die Notwendigkeit von Privatisierungen und der Wunsch nach öffentlichem Einfluss auf die ökonomische Entwicklung sich gegenseitig ausschließen. Zur Beantwortung dieser Frage werden die gegenwärtigen wirtschaftspolitischen Kompetenzen der Kommunen und der Rahmen zulässiger Privatisierungen dargelegt. Auf dieser Grundlage lässt sich klären, ob kommunale Wirtschaftspolitik durch Privatisierungen beschränkt wird. Soweit dies zutrifft, kann untersucht werden, ob diese Verluste sich durch andere vom Gesetz vorgesehene oder durch Vertrag vorzubehaltende kommunale Ingerenzrechte kompensieren lassen.

In recent times, environmental, energy and climate policies have gained tremendously in importance. Policy approaches to combat environmental pollution and climate change differ both in their intention and in their economic impacts. For instance, command-and-control instruments such as performance or technology standards have different implications than market-based mechanisms such as permit trading of greenhouse gas emissions. Furthermore, sectoral and regional characteristics play an important role when implementing and assessing policy measures. This applies both to the attainability of the targets and to the available instruments. The present doctoral thesis addresses this point and analyzes in several essays different policy instruments and their economic effects from global, regional and sectoral perspectives. In this respect, it deals with various, often very heterogeneous question: How are specific policy types implemented in different countries? What is the CO2 abatement potential in specific regions and sectors? What policy measures can be plausibly used to exploit this potential? How can technological developments and technology-directed policy interventions contribute to improve energy efficiency? Does the promotion of certain energy sources necessarily create positive production and employment effects? To answer these and further questions, different economic methods are applied that accommodate the particular problem, where special emphasis is put on computable general equilibrium modeling. The aim of this work is to contribute to the academic and political debate on measures to combat environmental and climate problems.
Keywords: Wirtschaftspolitik; Gemeinde; Kommunalrecht; Gemeindefinanzen; Verschuldung; Kommunale Selbstverwaltung; Privatisierung; Kompetenz; Wirkungsanalyse; Regulierung; Ingerenzrecht; Kompetenzverlust